Różne oblicza interwencjonizmu w rolnictwie na drodze do zrównoważonego rozwoju - Kułyk, Piotr (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The book addresses the problem of differentiation occurring in interventionism in agriculture and its multi-faceted conditions. The use of various forms of interventionism, both in developed and developing countries, leads to determining its paths and effects in individual countries and groups of countries. The challenge is not the issue of applying state intervention in agriculture itself, but the answer to the question: what should be the scale and under what conditions these activities can be used?
Keywords: interwencjonizm; zrównoważony rozwój; ekonomia rolna; ekonomia środowiska; finansowe wsparcie rolnictwa; interventionism; sustainable development; agricultural economics; environmental economics; financial support of agriculture